Analysis of Product and Cultural Diversity as an Opportunity to Increase Market Expansion From Shocked Markets to E.Commerce at Masjid Al-Falah Surabaya - Noneng R.Sukatmadiredja; Emmywati; Iwang Suwangsih; Nuzulul Fatimah (Journal of Islamic Economics Perspectives, 2021)
Analysis of product and cultural diversity as an opportunity to increase market expansion in shock markets towards E.Commerce at Masjid Al-Falah Surabaya", aims to analyze the opportunities created by the shock market to market opportunities with E.Commerse the market was shocked to become a digital market, namely E .commerce. The study was conducted at Masjid Al = Falah Surabaya with an unknown population, with a random sample of 40 respondents. Analysis of data by analyzing, purchasing activities caused by product diversity and cultural factors, these two variables can influence purchasing decisions, purchasing decisions can be increased repurchase through e.Commerce. The results showed that respondents who decided to buy were divided into buying because there were 26 respondents equal to 65%, respondents who did not buy 0, while 14 respondents who had impulse buying were equal to 35%. Whereas respondents bought goods because the quality of the product varied some 34 respondents, equivalent to 85%, respondents who bought because it was by the type of product were 32 respondents equal to 80%, while respondents bought because the price was cheaper were 37 respondents, equivalent to 92.5%, buying because the culture was 100%, whereas because of the sub-culture there are 8 respondents, namely 2%, while the social class of almost all social classes buys means 100%. The analysis of market increase can be seen from buyers who carry out repurchases, this can be seen from there are 11 respondents equivalent to 27.5% through electronic media, either WA, Instagram, or COD. It can be concluded that opportunities can be taken from the traditional market shock to the E.Commerce market.